Ultrahigh Dielectric Permittivity of a Micron-Sized Hf0.5Zr0.5O2 Thin-Film Capacitor After Missing of a Mixed Tetragonal Phase - Zhang, Wen Di; Li, Bing; Wang, Wei Wei; Wang, Xing Ya; Cheng, Yan; Jiang, An Quan (Nano-Micro Letters, 2025)
Innovative use of HfO2-based high-dielectric-permittivity materials could enable their integration into few-nanometre-scale devices for storing substantial quantities of electrical charges, which have received widespread applications in high-storage-density dynamic random access memory and energy-efficient complementary metal–oxide–semiconductor devices. During bipolar high electric-field cycling in numbers close to dielectric breakdown, the dielectric permittivity suddenly increases by 30 times after oxygen-vacancy ordering and ferroelectric-to-nonferroelectric phase transition of near-edge plasma-treated Hf0.5Zr0.5O2 thin-film capacitors. Here we report a much higher dielectric permittivity of 1466 during downscaling of the capacitor into the diameter of 3.85 μm when the ferroelectricity suddenly disappears without high-field cycling. The stored charge density is as high as 183 μC cm−2 at an operating voltage/time of 1.2 V/50 ns at cycle numbers of more than 1012 without inducing dielectric breakdown. The study of synchrotron X-ray micro-diffraction patterns show missing of a mixed tetragonal phase. The image of electron energy loss spectroscopy shows the preferred oxygen-vacancy accumulation at the regions near top/bottom electrodes as well as grain boundaries. The ultrahigh dielectric-permittivity material enables high-density integration of extremely scaled logic and memory devices in the future. Highlights: 1 Ferroelectric-to-nonferroelectric transition occurs in a micron-sized Hf0.5Zr0.5O2 thin-film capacitor with the generation of a giant dielectric permittivity. 2 Synchrotron X-ray micro-diffraction patterns show missing of a mixed tetragonal phase in the capacitor. 3 The stored charge density of the capacitor is as high as 183 μC cm-2 at an operating voltage/time of 1.2 V/50 ns at cycle numbers of more than 1012 without inducing dielectric breakdown.